2022
DOI: 10.1002/rth2.12686
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pharmacokinetics and reduced bleeds in boys with hemophilia A after switching to Kovaltry from other standard half‐life factor VIII concentrates

Abstract: Background BAY81‐8973 (Kovaltry; Bayer, Berkeley, CA, USA) was reported with enhanced pharmacokinetic (PK) profiles compared with some other standard half‐life (SHL) factor VIII (FVIII) concentrates. Limited head‐to‐head comparative studies were conducted in a real‐world setting. Objective To make head‐to‐head comparisons of PK and clinical outcomes between Kovaltry and three other SHL FVIII concentrates. Methods Forty‐seven boys with severe hemophilia A were enrolled and divided into three groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Data on inhibitor development related to factor switching in children are still scarce. In a recent publication, Huang et al reported that none of 47 boys aged less than 18 years switched to one of three standard half-life factors (Kovaltry, Advate, and GreeMono) developed inhibitor (14). Similar results were published by Escuriola-Ettinghausen et al however, only 14 out of 68 patients switched to turoctokog-alpha were younger than 12 years (15).…”
Section: Discussionmentioning
confidence: 56%
“…Data on inhibitor development related to factor switching in children are still scarce. In a recent publication, Huang et al reported that none of 47 boys aged less than 18 years switched to one of three standard half-life factors (Kovaltry, Advate, and GreeMono) developed inhibitor (14). Similar results were published by Escuriola-Ettinghausen et al however, only 14 out of 68 patients switched to turoctokog-alpha were younger than 12 years (15).…”
Section: Discussionmentioning
confidence: 56%
“…Another comparative PK study with rigorous head-to-head design also found that a patient could have his or her FVIII half-life time change up to 41% (from GreenMono to Kovaltry: 10.7 ± 1.7 h to 15.1 ± 3.4 h). 8 Thus, we suggest the authors explore more FVIII concentrates, especially for those that have been reported with shorter or longer half-life times.…”
Section: Dear Editormentioning
confidence: 98%
“…In my experience with more than 300 PK tests in pediatric patients with hemophilia, it would not be hard to control the dose within 40-60 IU/kg for the PK infusion despite different vial sizes. [6][7][8]10 But considering the wide use of WAPPS-Hemo, the dose could vary among different hemophilia centers. To facilitate clinical application, the authors might consider reporting corresponding suggested personalized sampling times by different common dose ranges.…”
Section: Dear Editormentioning
confidence: 99%
“…Thus, the authors could also seek PK parameters of different FVIII concentrates in published clinical trials as they are conducted in the Chinese population. Actually, the variability of PK parameters among different FVIII concentrates was also reported, which could be a potential bias for this study and there could have been better relevant descriptions in the limitations section [ 12 , 13 ].…”
mentioning
confidence: 99%